ANALISIS PERHITUNGAN DAN PELAPORAN PPh PASAL 23 ATAS PENDAPATAN PERUSAHAAN PADA PT.JAGAD TOTAL LOGISTIC EXPRESS - Erren Imaniar Rizqi; Agus Subandoro (LPPM Universitas Bina Bangsa, 2022)
Tax is a mandatory contribution or contribution paid by the people or taxpayers to the state for the benefit of the government and the welfare of the community. Revenue is income arising from the company's activities which are commonly known by different names such as sales, sales of services (fees), interest, dividends, royalties and rent. Meanwhile, the purpose of this research is to find out the procedure for calculating and reporting company income at PT. Jagad Total Logistic Express and whether it is in accordance with Tax Law no. 36 of 2008 and 141/PMK.03/2015. In this study, the research method used was descriptive quantitative. This study will discuss the problem by collecting, describing, calculating, and comparing a situation and explaining a situation. From the research results show that the calculation of PPh. Article 23 is subject to a 2% rate and it can be concluded that the calculation and reporting of Income Tax Article 23 on Company Revenues at PT. Jagad Total Logistic Express is fully in accordance with Tax Law no. 36 of 2008 and 141/PMK.03/2015